A novel CRX frameshift mutation causing cone-rod dystrophy in a Chinese family: A case report - Wang, Lihua (Medicine (Baltimore), 2018)
BACKGROUND: Cone-rod dystrophy (CORD) is an inherited, progressive retinal disorder with genetic and phenotypic heterogeneity. Here, we aimed to identify the pathogenic mutation in affected individuals in a Chinese family with autosomal dominant cone-rod dystrophy (adCORD). METHODS: Genomic DNA and clinical examination results were collected from a Chinese family presenting with adCORD. The candidate disease-causing mutations were screened with whole-exome sequencing (WES) and bioinformatics analyses. Sanger sequencing was used for validation and cosegregation analysis. RESULTS: A novel frameshift mutation (NM_000554.4; c.538dupG:p.Val180fs) in exon 4 of the CRX gene was identified in all affected individuals in the Chinese family with adCORD. Cosegregation analysis confirmed that this mutation was cosegregated with the disease. This variant, which results in premature termination of the protein, was absent from all public variant databases or internal exome databases. CONCLUSIONS: We used whole-exome sequencing to identify a novel CRX mutation causing adCORD in a Chinese family. This study broadens the known pathogenic mutation spectrum of the CRX gene and shows the potential of WES in identifying the pathogenic mutations of CORD disease.